The role of polytechnics and the industry on the marketability of Johore polytechnics graduates in the field of engineering. - Zamri, Fakrul Faris (2023)
Even though we have entered the industry 4.0 era, the issue of graduate marketability is still a widely discussed issue in various fields due to the high number of unemployed graduates. This descriptive study aims to identify the role of polytechnics and the industry on the marketability of Johore polytechnic graduates in the field of engineering. This study aims to answer the research questions, which correspond to three research objectives, namely identifying the role of the polytechnic, the role of industry (from the perspective of the Polytechnic) and improving the quality of the curriculum. The study is a quantitative study and the data were collected using a set of questionnaires. The questionnaire is divided into 3 parts, 2 parts contain a set of closed item questions and 1 part with open-ended items, namely Part A for demographic data, Part B is about the marketability factor of polytechnic engineering diploma graduates and Part C is the opinion section, complaints and suggestions. The selection of respondents for this study consists of 23 respondents representing 3 institutions of Engineering Polytechnic in Johor. The results of the study were analysed using Statistical Package for Social Science (SPSS) version 26.0. Overall, the mean value of the marketability factors of Johore polytechnic graduates in in the field of engineering is at a high specifically, the role of polytechnics (4.46), the role of industry from the polytechnic perception (4.18) and curriculum quality improvement (4.42). The findings of this study will provide information to the relevant parties on measures to improve TVET education in Malaysia.